Kelas Hypnobirthing Sebagai Mind-Body And Interventions: Study Kualitatif Di Puskesmas Rawat Inap Kota Yogyakarta - Ari Andriyani; Jusuf Sulaeman; Dewi Marhaeni (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2016)
Background: The number of pregnant women experiencing anxiety tends to increase. It affects both maternaland fetal outcome, physically and mentally health of the fetus. Hypnobirthing is a mind-body intervention to reduceanxiety, fear, panic, and tension during pregnancy and childbirth.Objective: To explore perception or hypnobirthing response as mind-body intervention in preparing for labor andbirth.Method: Qualitative design with phenomenology strategy, done with in-depth interview technique. The qualitativesample was conducted by purposive sampling on 17 informants. The research was conducted in Mergangsan,Jetis, and Tegalrejo District of Yogyakarta City from January to April 2014, analyzing qualitative data with contentanalysis.Results: Class hypnobirthing reduces pain, shortens labor stage I and stage II, lowers feelings of tension, worriesbad, fear, nervous, anxious, hesitant, worried and confused, and increase feelings of satisfaction, self-confidence,relaxed, meaningful, steady and happy.The success of hypnobirthing in reducing anxiety is influenced by family support, birthplace comfort, relaxationfacilities, and disturbance of tranquilityConclusion: hypnobirthing participants feel fulfilled their physical, emotional and spiritual needs during pregnancyand childbirthKeywords: The class hypnobirthing, childbirth anxiety